AI Implementation Impact on Workforce Productivity : The Role of AI Training and Organizational Adaptation - Nurlia, Nurlia; Daud, Ilzar; Rosadi, Muhammad Edya (Escalate : Economics and Business Journal, 2023)
This study investigates the impact of AI implementation on workforce productivity, focusing on the mediating roles of Organizational Adaptation and AI Training. The purpose of the research is to analyze how AI Implementation influences Organizational Adaptation and AI Training, and subsequently, how these factors impact Workforce Productivity within the context of the Regional Secretariat Pontianak. A quantitative approach is employed, using a sample of 70 employees through total sampling. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) is used for data analysis. The findings reveal significant and positive relationships between AI Implementation, AI Training, Organizational Adaptation, and Workforce Productivity. The implications highlight the importance of comprehensive strategies that integrate AI technologies, training initiatives, and organizational flexibility to enhance productivity